TOWARDS ADVANCED DEVELOPMENT OF CYBORG INTELLIGENCE - R, Dewi Agushinta; Rindani, Fiena; Kurniawan, Antonius Angga; Anggari, Elevanita; Akbar, Rizky (Jurnal Ilmiah Informatika Komputer, 2018)
The creation of machines with human intelligence is an primary and beneficial aim of artificial intelligence research. One interesting method in developing artificial intelligence is combining a biological method and machine intelligence. Cyborg Intelligence is a new scientific model for the integration of biological and machinery. Brain Machine Interface (BMI) provides an opportunity to integrate both intelligence at various levels. Based on BMI, neural signals can be read for the control of motor actuators and sensory information coding machine can be sent to a specific area of the brain. In fact, Distributed Adaptive Control Theory of Mind and Brain technology is the most advanced brain-based cognitive architecture successfully applied in a wide range of robot tasks. It is expected that by analyzing the cyborg intelligence development can help and facilitate to enhance the knowledge of cyborg intelligence.